Decadal biomass increment in early secondary succession woody ecosystems is increased by CO2 enrichment - Anthony P. Walker (Nature Portfolio, 2019)
It is unclear whether CO2-stimulation of photosynthesis can propagate through slower ecosystem processes and lead to long-term increases in terrestrial carbon. Here the authors show that CO2-stimulation of photosynthesis leads to a 30% increase in forest regrowth over a decade of CO2 enrichment.